Clinical observation of three-step modified shoulder joint mobilization for scapulohumeral periarthritis - Lü, Zhi-gang; Zhu, Jun; Hu, Wei-cheng; Ning, Chun-rui (Journal of acupuncture and tuina science, 2016)
Objective To observe the clinical efficacy of the three-step modified shoulder joint mobilization in treating scapulohumeral periarthritis (SP). Methods Totally 80 subjects were recruited and divided into a treatment group and a control group by using the random number table, 40 in each group. The treatment group was intervened by the three-step modified shoulder joint mobilization; the control group was by oral administration of Celebrex. After successive 4-week treatment, the improvement of shoulder pain and motor function was observed. Results The total effective rate was 87.5% in the treatment group versus 80.0% in the control group, and the difference was statistically significant ( P <0.05). Conclusion The three-step modified shoulder joint mobilization is easy-to-operate and effective in treating SP.